Penerapan Prinsip-Prinsip Good Corporate Governance (GCG) pada Perusahaan Properti - Susanti, Rahayu Eka; Dyah Ratnawati (Jurnal Akutansi Manajemen Ekonomi Kewirausahaan (JAMEK), 2025)
This study aims to examine the implementation of Good Corporate Governance (GCG) in Property Companies. It also seeks to understand how well GCG principles are applied in accordance with relevant regulations. Thestudy employs a qualitative descriptive methodology, using a property company as a case study. Secondarydata such as annual reports, internal archives, and scientific journal publications are analyzed through libraryresearch and documentation. Data analysis is conducted using a qualitative descriptive approach, includingdata reduction, categorization, verification, and interpretation.The analysis results show that the propertycompany has effectively and consistently applied GCG principles. Transparency is demonstrated through thepublication of annual reports, dissemination of accurate information, and protection of whistleblowers.Accountability is implemented through a clear governance structure, well-defined job descriptions, and aneffective internal control system in accordance with the Sarbanes-Oxley Act (SOA 404). Performance ismeasured using Key Performance Indicators (KPIs).Responsibility is reflected in legal compliance, active CSRprograms, and integrated risk management. Independence is maintained through the autonomous roles of theBoard of Directors, the Board of Commissioners, and the Audit Committee. Fairness and equality are shownthrough non-discriminatory treatment of shareholders, gender equality, a meritocracy system, and policies thatprioritize all stakeholders in line with the AKHLAK values (Trustworthy, Competent, Harmonious, Loyal,Adaptive, and Collaborative). The implications of optimal GCG implementation include enhanced reputation,protection of involved parties, legal compliance, and improved operational performance and businessvaluation. GCG also fosters increased investor trust through transparency and careful management. This iscrucial in promoting competent, effective, and efficient management of State-Owned Enterprises (SOEs), aswell as strengthening independence and improving the operational performance of important corporateorganizations.